Christian Social Justice in Indonesia: The Role of the Church in Addressing Inequality and Environmental Injustice (Indonesian Theological Justice Review, 2025)
The Christian Church in Indonesia has a long history of involvement in social justice movements, addressing issues such as inequality, labor exploitation, and environmental degradation. This paper examines the role of the Indonesian Church in promoting social and environmental justice, particularly in areas affected by deforestation, mining, and labor rights abuses. The study explores Christian social justice theology, including concepts like the preferential option for the poor and stewardship of creation, and how these principles have motivated church-led initiatives aimed at reducing inequality and promoting sustainability. The paper investigates the Church’s involvement in advocacy for marginalized communities, including workers in the palm oil industry, and its engagement with environmental protection efforts, particularly in the wake of Indonesia’s environmental crisis. The paper also evaluates the effectiveness of the Church’s role in promoting social change, considering both successes and challenges. Finally, it offers recommendations for enhancing the Church’s involvement in both social and environmental justice movements, suggesting greater collaboration with secular organizations, grassroots movements, and policy-makers to address these pressing issues.